2008
DOI: 10.1128/cvi.00169-08
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunization with RecombinantLactobacillus plantarumInduces a Protective Immune Response in Mice with Lyme Disease

Abstract: Mucosal immunization is advantageous over other routes of antigen delivery because it can induce both mucosal and systemic immune responses. Our goal was to develop a mucosal delivery vehicle based on bacteria generally regarded as safe, such as Lactobacillus spp. In this study, we used the Lyme disease mouse model as a proof of concept. We demonstrate that an oral vaccine based on live recombinant Lactobacillus plantarum protects mice from tick-transmitted Borrelia burgdorferi infection. Our method of express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 66 publications
2
60
0
1
Order By: Relevance
“…Oral immunization has been shown to provide protection against a variety of bacterial pathogens, including Vibrio cholerae, Salmonella enterica serovar Typhi, and Borrelia burgdorferi (12)(13)(14)(15). Protection of mice against B. burgdorferi infection by oral immunization has been achieved using either Lactobacillus plantarum (12) or Escherichia coli (15) as delivery vehicles for the immunogen, OspA. Inclusion of the 16-amino-acid lipoprotein signal peptide of OspA tags the protein for translocation across the cytoplasmic membrane and subsequent lipidation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oral immunization has been shown to provide protection against a variety of bacterial pathogens, including Vibrio cholerae, Salmonella enterica serovar Typhi, and Borrelia burgdorferi (12)(13)(14)(15). Protection of mice against B. burgdorferi infection by oral immunization has been achieved using either Lactobacillus plantarum (12) or Escherichia coli (15) as delivery vehicles for the immunogen, OspA. Inclusion of the 16-amino-acid lipoprotein signal peptide of OspA tags the protein for translocation across the cytoplasmic membrane and subsequent lipidation.…”
mentioning
confidence: 99%
“…Orally delivered vaccines have several advantages over other routes of antigen delivery, including convenience, costeffectiveness, and, most importantly, induction of both local and systemic immune responses (11). Oral immunization has been shown to provide protection against a variety of bacterial pathogens, including Vibrio cholerae, Salmonella enterica serovar Typhi, and Borrelia burgdorferi (12)(13)(14)(15). Protection of mice against B. burgdorferi infection by oral immunization has been achieved using either Lactobacillus plantarum (12) or Escherichia coli (15) as delivery vehicles for the immunogen, OspA.…”
mentioning
confidence: 99%
“…Their abilities to transit through the stomach intact and to associate closely with the intestinal epithelium, combined with their immunomodulatory properties, have made Lactobacillus spp. attractive candidates as live vehicles for the delivery of immunogens to the intestinal mucosa (6,12). It was recently shown that specific Lactobacillus species can induce inflammatory responses against infection, increase IgA production, activate monocytic lineages (4,16), and regulate the balance of the Th1 and Th2 pathways (2,30).…”
mentioning
confidence: 99%
“…Taking advantage of these characteristics, previous studies using recombinant DNA technology have used lactobacilli to express or secrete useful proteins. 3,5) Cholera is a diarrheal infection disease caused by Vibrio cholerae, with an estimated 3-5 million cholera cases and 100000-120000 deaths due to cholera every year. 6) Cholera toxin (CT) is comprised of a toxic A (CTA) subunit and a pentameric non-toxic B (CTB) subunit.…”
Section: Expression and Secretion Of Cholera Toxin B Subunit In Lactomentioning
confidence: 99%